Application of Process Portofolio Assessment Based on Guided Inquiry Model in Improving Critical Thinking Skills and Learning Outcomes of Science Education Students - Ummiy Fauziyah Laili*; Zakiyatus Soimah; Atika Anggraini; Sayyidah Auliayur Rohmah; Rahmawati Yanita Sari (Universitas Syiah Kuala, 2023)
Critical thinking skills are one of the skills that must be possessed by human resources in the 21st century. In fact, the critical thinking skills of science education students have not been properly empowered. The design of this research is quasi-experimental research. The research population used was all Science Education students at IAIN Kediri. The sample used in this study were two classes of Batch 2022, namely class A and class B. Data collection was carried out using a pretest and posttest to measure critical thinking skills, process portfolio assessment, observation of student attitudes and skills learning outcomes. The results showed that there was a positive effect from the implementation of the process portfolio assessment on students' critical thinking skills and biology learning outcomes. The conclusion that can be drawn is that the application of process portfolio assessment in the guided inquiry model causes higher critical thinking skills and student biology learning outcomes